Hypertension and COVID-19: Ongoing Controversies - Tadic, Marijana; Saeed, Sahrai; Grassi, Guido; Taddei, Stefano; Mancia, Giuseppe; Cuspidi, Cesare (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease 2019 (COVID-19) has become a worldwide pandemic responsible for millions of deaths around the world. Hypertension was identified as one of the most common comorbidities and risk factors of severity and adverse outcome in these patients. Recent investigations raised the question whether hypertension represents a predictor of outcome in COVID-19 patients independently of other common comorbidities such as diabetes, obesity, other cardiovascular diseases, kidney, liver and pulmonary chronic diseases. Additionally, the impact of chronic and newly diagnosed hypertension in COVID-19 patients has been insufficiently investigated. The same is valid for the relationship between blood pressure level and outcome in COVID-19 patients. It seems that long discussion about the impact of angiotensin-converting enzyme inhibitors (ACEI) and blockers of angiotensin I receptors (ARB) on severity and outcome in COVID-19 is approaching to its end because the large number of original studies and meta-analyses discarded the initial findings about higher prevalence of ACEI/ARB use in patients with unfavorable outcome. Nevertheless, there are many controversies in the relationship between hypertension and COVID-19. The aim of this review article is to provide clinical overview of the currently available evidence regarding: predictive value of hypertension, effect of blood pressure level, impact of previously known and newly-diagnosed hypertension, and antihypertensive therapy on severity and outcome in COVID-19 patients.